The GAIN Short Screener (GSS) as a Predictor of Future Arrest or Incarceration among Youth Presenting to Substance Use Disorder (SUD) Treatment. (January 2013) - Garner, Bryan R.; Belur, Vinetha K.; Dennis, Michael L.
The National Institutes of Health (NIH) data harmonization project on existing measures (www.phenx.org ) has recommended the Global Appraisal of Individual Needs (GAIN)–-Short Screener (GSS) as one of the most reliable, valid, efficient, and inexpensive general behavioral health screeners to quickly identify people with internalizing and externalizing mental health disorders, substance use disorders, and crime/violence problems. The present study examined how well the four GSS screeners and their sum predict future arrest or incarceration among individuals entering treatment for a substance use disorder. Using a cross-validation design, a diverse sample of 6, 815 youth with substance use disorders was split into a development sample and a validation sample. Overall, results found the GSS's crime and violence screener (CVScr) and the substance disorder screener (SDScr) to be the two best predictors of arrest/incarceration within the 12 months following treatment intake. Additionally, we found that these screeners could be used to categorize individuals into three groups (low risk, moderate risk, high risk) and this simplified classification had good predictive validity (Area Under the Curve = 0.601). In sum, the GSS's predictive validity was similar to other instruments that have been developed to predict risk for recidivism; however, the GSS takes only a fraction of the time to collect (ie, approximately 2–3 minutes for just these two screeners).